EVALUATION OF CORPORAL COMPOSITION THROUGH THE BIOIMPEDANCE AND ANTHROPOMETRY METHOD IN MILITARY POLICEMEN AND FIREMEN (Fiep Bulletin - online, 2014)
Objective: Compare body composition by bioelectrical impedance analysis and anthropometric methods applied to military policemen and firemen in the city of Guarabira-PB, working in the operational service of the 4th Military Police Battalion and 3rd Battalion Fire Brigade. Methods: The research dealt with is a cross-sectional descriptive study consisting of 50 military policemen and 52 firemen male soldiers, consisting of a sample of the non-probabilistic convenience. For this study, we surveyed about age, gender, body mass, height, Body Mass Index (BMI) and body fat percentage. Results: The nutritional diagnosis more frequent in the population studied was overweight and obesity, being 32 (64%) in the policemen and 33 (63.4%) in the firemen. The group analyzed showed values ??for the percentage of fat in both the methods used above the normal range established by the World Health Organization (WHO) is 15% and thus at high risk for metabolic complications. Conclusion: This study showed the prevalence of overweight in military policemen and firemen, thus suggesting that there is need for greater physical activity and dietary reeducation groups evaluated. The implementation of health policies aimed at preventing obesity certainly will have a major impact on primary prevention of chronic diseases in these individuals, improving the physical condition required in the work that they realized.
Keywords: Obesity; Body Composition; Military